Luftlinie : Wien-Hamburg 1989/90. - Hofmann, Werner; Lachmayer, Herbert; Stadt Hamburg (Wien: Stadt Wien, 1989)
Borek, Alexander ; Brockmann, Jürgen ; Täubl, Helmut ; Ro, Ein Nim ; Odenwald, Ralf-Rainer ; Rebec, Jadranko ; Schmid, Richard Peter ; Conrad, Martin ; Schu, ManfreDu ; Priesch, Hannes ; Walde, Martin ; Jurszo, Ralf ; Reitberger, Peter ; Troger, Gustav
biografie
Luftlinie, Wien 1989 ; Hamburg 1990
Duits
kunstcatalogus